Different times, same methods: The impact of the National Security Service on the operations of the National Intelligence and Security Agency - Sinkó, Gábor (Journal of Central and Eastern European African Studies, 2024)
This article examines the impact of the National Security Service (NSS) on the operations on the National Intelligence and Security Agency (NISA). It begins with the short history of Somalia between 1960 and 1991 and then the article analyzes the activities of the NSS, the main intelligence apparatus of the Siad Barre regime, and the NISA, the primary intelligence service of the Federal Government of Somalia (FGS). It contends that instead of reestablishing the NISA as an organization serving the interests of the general public, it continues to operate as an instrument of political power. The study argues that although times may differ, methods remain the same when scrutinizing the operations of these Somali intelligence apparatuses. There are many common features characterizing the agencies, including the governments’ use of these intelligence services for the consolidation of their personal power, getting rid of political opponents or conducting extrajudicial activities. The interconnectedness of military and political power, the dominance of patron-client relationships, the conduct of intelligence and counterintelligence operations in neighboring countries, and the prioritization of clan loyalty are additional similarities. The reconfiguration and reorganization of the security sector is needed for peace to be restored in the country.